A review of 5G technology: architecture and challenges - Attarbashi, Zainab; Abdulazeez E., Altaleb; Azana Hafizah Mohd, Aman; Aisha, Hassan Abdalla Hashim; Sebahattin, Eker (2022)
5G Networks are considered as a new evolution since it aims to increase the wireless capacity 1000 times the previous generations. It is the networks that enabling the Internet of Things (IoT) and the Internet of Everything (IoE) by connecting 7 billion people and 7 trillion “things” while saving 90% Energy and perceiving Zero Latency. In this article, we summarize the deployment requirements and challenges of 5G Networks. First, the overall network architecture and network slicing framework including the service-type slicing and the infrastructure slicing are investigated. Later, the spectrum and multiple access techniques are explained. Finally, the challenges and the available solutions have been discussed.